2020
DOI: 10.1177/1533317520918719
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Sensitivity of Alzheimer’s Disease Severity Staging

Abstract: Understanding Alzheimer’s disease (AD) dynamics is essential in diagnosis and measuring progression for clinical decision-making; however, clinical instruments are imperfect at classifying true disease stages. This research evaluates sensitivity and determinants of AD stage changes longitudinally using current classifications of “mild,” “moderate,” and “severe” AD, using Mini-Mental State Examination (MMSE), Alzheimer’s Disease Assessment Scale–Cognitive subscale (ADAS-Cog), and the Clinical Dementia Rating–Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…These combinations can therefore be potentially useful biomarkers for tracking the progression of AD, however there is a stronger support for using the relationship between MMSE and ventricular volume. This is also supported in a recent study which found that the sensitivity of MMSE (∼92%) (but similar to that of ADAS-cog) supersede that of CDR-sum (∼78%) for the identification of changes associated with the clinical stages of AD longitudinally (91).…”
Section: Discussionsupporting
confidence: 75%
“…These combinations can therefore be potentially useful biomarkers for tracking the progression of AD, however there is a stronger support for using the relationship between MMSE and ventricular volume. This is also supported in a recent study which found that the sensitivity of MMSE (∼92%) (but similar to that of ADAS-cog) supersede that of CDR-sum (∼78%) for the identification of changes associated with the clinical stages of AD longitudinally (91).…”
Section: Discussionsupporting
confidence: 75%
“…AD patients fulfilled the National Institute on Aging and Alzheimer's Association (NIA-AA) criteria for probable AD dementia [37]. They also fulfilled the AD Neuroimaging Initiative (ADNI) criteria for AD in terms of MMSE, CDR, and LM-IIA scores [38], except that we included patients with moderate AD based on Benoit et al's criteria [39]. Specifically, AD patients fulfilled the following criteria: MMSE score 10-26; the CDR global score 0.5 or 1; and LM-IIA score ≤8 for 16 years of education (YoE), ≤4 for 8-15 YoE, and ≤2 for 0-7 YoE.…”
Section: Participantsmentioning
confidence: 99%
“…Due to science, computer-aided diagnosis systems (CADs) were developed to play an important role in enhancing the understanding of medical imagery among researchers and physicians. The application of the machine learning technique, in particular DL strategies in CAD models to diagnose and classify stable control patients with average (CN), AD, and mild cognitive impairment (MCI), has exponentially grown [ 21 , 22 ]. The automatic diagnosis of AD performs an essential role in human health, especially in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several scholars have discussed using image classification to carry out AD diagnosis. Several DL approaches have been suggested to use MRI images to introduce multiple AD patients' severity [ 22 , 23 ]. The higher the image quality, the better the outcomes achieved, known in image analysis.…”
Section: Introductionmentioning
confidence: 99%